Oscillatory Solutions Of Fourth- Order Delay Difference Equations With Damp - et. al., R. Kodeeswaran, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research work concerned with new oscillatory solutions of Fourth-order delay difference equations with damping term of the form ∆(